PERTUMBUHAN PENDUDUK BESUKI: KAJIAN DEMOGRAFI HISTORIS - Nawiyanto Nawiyanto (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2009)
In demographic terms, Besuki residency was a distinctive region comparedwith the rest of Java. It is argued that demographic growth taking place in the region was linked primarily to migration, rather than births and deaths. Drawing upon diverse historical materials, this article discusses the role of migration and natural factors of births and deaths, in populating the region of Besuki by comparing it with Java. In elaborating the arguments, this article specifically looks at factors and conditions that affected each component and its contribution to the demographic process in the region.